2008
DOI: 10.2147/tcrm.s2379
|View full text |Cite
|
Sign up to set email alerts
|

A review of nasal polyposis

Abstract: Nasal polyps are common, affecting up to four percent of the population. Their etiology remains unclear, but they are known to have associations with allergy, asthma, infection, cystic fi brosis, and aspirin sensitivity. They present with nasal obstruction, anosmia, rhinorrhoea, post nasal drip, and less commonly facial pain. Clinical examination reveals single or multiple grey polypoid masses in the nasal cavity. Computerized tomography allows evaluation of the extent of the disease and is essential if surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
131
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(152 citation statements)
references
References 43 publications
5
131
0
8
Order By: Relevance
“…Also the nasal polyps before VD taking in the present study showed damage of respiratory epithelium that rests on thick basal lamina with numerous inflammatory cells infiltration, extensive accumulation of collagen fibers in lamina propria and highly expressed TLR-9 and these results were agreed with [23][24][25] who reported that the histological appearance of NP is characterized by respiratory epithelium with a range of mucosal alterations that include ulceration, thickening of the basement membrane, near normal nasal mucosa with overcrowded respiratory epithelium rests on apparently thin basal lamina and lamina propria of loose connective tissue with few cells infiltration and many blood vessels and showed significant decrease (P<0.05) in all symptoms of VAS score and endoscopic appearance of Lund and Mackey score and the mean area % of submucosal accumulation of collagen fibers and TLR-9 expression while this decrease was insignificant (P < 0.05) in the low dose VD group (IIa). These results agreed with [39] who reported that the antiproliferative effects of VD were dose-and timedependent, the lower concentration used was mostly without any effect and [40] stated that in the overall study population of Finnish VD Study, clinical outcomes appeared to favor the high-dose VD group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Also the nasal polyps before VD taking in the present study showed damage of respiratory epithelium that rests on thick basal lamina with numerous inflammatory cells infiltration, extensive accumulation of collagen fibers in lamina propria and highly expressed TLR-9 and these results were agreed with [23][24][25] who reported that the histological appearance of NP is characterized by respiratory epithelium with a range of mucosal alterations that include ulceration, thickening of the basement membrane, near normal nasal mucosa with overcrowded respiratory epithelium rests on apparently thin basal lamina and lamina propria of loose connective tissue with few cells infiltration and many blood vessels and showed significant decrease (P<0.05) in all symptoms of VAS score and endoscopic appearance of Lund and Mackey score and the mean area % of submucosal accumulation of collagen fibers and TLR-9 expression while this decrease was insignificant (P < 0.05) in the low dose VD group (IIa). These results agreed with [39] who reported that the antiproliferative effects of VD were dose-and timedependent, the lower concentration used was mostly without any effect and [40] stated that in the overall study population of Finnish VD Study, clinical outcomes appeared to favor the high-dose VD group.…”
Section: Discussionsupporting
confidence: 88%
“…Nasal polyposis is a common nasal disease with a high rate of recurrence [21]. The patients of nasal polyps before VD taking (groups IIb and IIIb) in our study presented with symptoms of VAS score (facial pain, headache, nasal blockage, nasal discharge, post-nasal drip and olfactory disturbance) and endoscopic appearance of Lund and Mackey score (polypi, edema and discharge) and this agreed with [22] and [23] who reported that nasal polyps are benign edematous masses in the nasal cavities, paranasal cavities, or both that can cause nasal obstruction, rhinorrhea, postnasal drip, loss of smell and facial pain and doi: 10.7243/2055-091X-1-2 avascular edematous stroma with submucosal fibrosis and an often prominent mixed inflammatory infiltrate. On the other hand [26] stated that the histopathologic features of a nasal polyp include hyperplasia of surface epithelium and goblet cells but [27] explain this as he reported that in NP the epithelial damage followed by aberrant tissue repair and structural changes (remodeling).…”
Section: Discussionsupporting
confidence: 85%
“…The main aims of the treatment are to eliminate or to significantly reduce the size of the nasal polyps to relieve the nasal obstruction, improvement in the sinus drainage and restoration of the olfaction. With both the treatments, recurrences are common, particularly in patients with asthma [16].…”
Section: Discussionmentioning
confidence: 99%
“…1 It is the most common non-neoplastic lesion in the nasal cavity. It also is a very common cause of chronic nasal obstruction.…”
Section: Introductionmentioning
confidence: 99%